THE FUTURE OF CSR/SUSTAINABILITY IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
As a part of the United Nations, Indonesia is participating in sustaining the world by enacting several regulations regarding Corporate Social Responsibility (CSR). Research publications on CSR/sustainability show the CSR/sustainability implementation and reflect how academicians view CSR/sustainability. Based on systematic literature review methods (Snyder, 2019) this study is trying to assess the advancement of CSR/sustainability In Indonesia, its antecedents and consequents, and the agenda for the next research. This study highlights the scholar's perspective on CSR/Sustainability implementation through articles published in Indonesian journals which are listed on SINTA (Science and Technology Index), the prominent research database in Indonesia. Furthermore, this study provides the direction for the future of CSR/Sustainability in Indonesia. Publications on CSR/Sustainability in Indonesia from the year 2008 to 2019 indicate that CSR/Sustainability is perceived as an additional task for the business to do rather than as a strategy for the whole business.
Keywords: CSR; Sustainability; Systematic Literature Review